An Experimental Study on Micro-Enhanced TESM Incorporated Inside Evacuated Tube Solar Collector Equipped with Heat Pipe - Alshukri, Mohammed J.; Eidan, Adel A.; Najim, Saleh Ismail (Basrah Journal for Engineering Sciences, 2021)
The incorporation of thermal energy storage materials (TESMs) into solar energy systems is a factor that boosts the performance of these systems. In this paper, an experimental study was addressed for enhancing the heat pipe’s thermal performance that works with an Evacuated Solar Tube Collector with Heat Pipe (ETCHP) as a solar water heater system. This is done by adding micro-zinc oxide (ZnO-MP) to the paraffin wax integrated as TESM into the evacuated tube (ET) of the system, where the evaporator section of the heat pipe is completely submerged within the micro-enhanced paraffin wax. Three experimental prototype rigs with one evacuated tube were designed, built, and tested to do the investigation. The most important parameters that have been studied in this study are the thermal resistance and the temperature distribution pattern along the heat pipe. The results show a clear indication of the decrease in the thermal resistance of the heat pipe of the proposed system compared to the system in which pure paraffin wax was incorporated. Also, it was noticed that there is a significant improvement in the temperature distribution along the heat pipe due to the improvement in the conductivity of the micro-enhanced wax compared to the pure wax.